A 31 L multilevel inverter topology with less switching devices for hybrid electric vehicle applications - K. Saravanan; M. Sivasubramanian; N. P. Gopinath; K. Kumarasamy; R. Azhagumurugan (Scientific Reports)
Abstract In this article, a 12 switch 31 L multi-level inverter (MLI) is proposed with the benefits of least switching devices for electric vehicle applications. In most electric vehicles (EV), conventional inverters are utilized so the lifetime of electric vehicle induction motors is reduced due to the high THD level and high voltage stress. To rectify this, a new inverter topology is proposed with minimum switching devices by increasing the level to 31, and also the THD should be maintained within IEEE standards. This inverter topology is constructed with variable DC sources (PV system) along with required capacitors and a polarity changer. The specific feature of this topology is that it can generate any level of voltage with minimum switching devices, less voltage stress, minimum THD, and less cost are tabulated in the comparison. This type of inverter can also applicable for high voltage (HV) applications and grid-connected systems. Furthermore, the proposed topology is simulated with MATLAB software and the downscale prototype model is developed using the DSPIC30f2010 controller.